PARTISIPASI MASYARAKAT DALAM PENGEMBANGAN EKONOMI MELALUI PROGRAM DESA WISATA DI DUSUN BINANGUN DESA PLINTAHAN - Putri Amalia Firdaus; Isna Fitria Agustina (T JDP (JURNAL DINAMIKA PEMERINTAHAN), 2025)
Collaborating between the public and education sectors, improving access to resources, and strengthening communities are the objectives of this research. A major focus of economic development studies has been community engagement in local economic development. This initiative strengthens social relations and economic growth. Data analysis was conducted through observation, interviews, literature review, and documentation. Primary data consists of information collected directly in the field through in-depth interviews with community informants and business owners. The results of the analysis show that community participation in the planning and evaluation stages is in the medium or good category. At the implementation and utilization stages, community participation is also very good. Residents of Binangun Hamlet in Plintahan experienced socioeconomic impacts. The village reduces poverty and unemployment by providing opportunities to work together, expand knowledge and insights, increase income, and create jobs through collaboration between residents